A foreign body that has been left for 20 years causes a pseudoaneurysm of the middle cerebral artery: a case report - Qiang Li; Zhengfang Jiang; Miao Yuan; Chenglang Xu; Lingyong Zeng (Journal of Medical Case Reports, 2024)
Abstract Background We report a patient with extensive subarachnoid hemorrhage caused by the rupture of a middle cerebral artery pseudoaneurysm from a foreign body that had been left for two decades. Case presentation A 74-year-old male patient from Han nationality was admitted to the emergency department of our hospital with impaired consciousness for 1 hour. Cranial computed tomography examination indicated a massive subarachnoid hemorrhage with intraventricular blood accumulation, and a high-density short strip dense shadow was seen in the M1 segment of the right middle cerebral artery, considering the possibility of a foreign body. Subsequently, a cerebral angiography was suggested; the foreign body was seen through the right middle cerebral artery, and the aneurysm was seen in the lower wall, so a pseudoaneurysm was considered. The emergent surgical intervention involved the clipping of the pseudoaneurysm and intracranial extraction of the foreign body. Unfortunately,the patient ultimately expired due to severe pulmonary infection. Conclusion Intracranial pseudoaneurysm caused by foreign body has been rarely reported previously, and microsurgical treatment of an intracranial pseudoaneurysm caused by a foreign body is a good choice.